Humanistic Poets And Classical Philosophy - Blum, Wilhelm (ETHICS IN PROGRESS, 2016)
The aim of the article is to show that the so-called “philosophia perennis” is valid for our modern times too. Four philosophical schools of the Hellenistic times remain influential for the following centuries: Plato and Neoplatonism, Aristotle and the Peripatetics, the Stoics and the Epicureans. We are interpreting two, only two, poems from Thomas More and Jacob Balde, and so we see the greatest possible influence of all these four ancient philosophical schools.